STUDI PENCIPTAAN KARYA PERFORMANCE ART DENGAN FOKUS EKSPLORASI RUANG DAN CAHAYA - Isnanta, Satriana Didiek (Acintya, 2010)
Study the creation of works of performance art â€œThe Light of Clear Soulâ€ is a study of the creation of works that explore the performance art, space and light. The form of mywork is explores space, practical and elastic that can be presented anywhere, either in the conventional stage, in the parks, in the forest, in a public toilet, or on the street. The form and the essence of its performance over the motion and the selected symbol. In this work performance, the light becomes important as one of the aesthetic elements. This work not only in the spot light like a standard show, but also flexible in accordance with the conditions and needs, such as spot lights, flashlights, lanterns, candles, or even a slide projector or video projector though. This work is actually very open, kind of ideas and forms. Even open to get in on the area of collaborative work. With my idea of an artist as a performer and installator (because of my art background) then no wonder I create works that will be open to the other performer-based dance, music and theater. The study uses the method of creation is the creation of works that have several stages of phase observation, experimentation phase and creating phase works. In the observation phase in addition to the observations of some performance art in person and also the documentation of a location that will be used. It is given such importance in the performance art space. Furthermore, the findings were used by the author as the basis for the creation of premises experimentation space and light which then continued into a work of performance art intact. Forms of performance art whose works are just that moment will be tricked by audiovisual documentation that could later be accounted for in a long time. Keywords: Performance art, space, light, experimentation